2019
DOI: 10.1002/ppul.24605
|View full text |Cite
|
Sign up to set email alerts
|

Therapies that are available and under development for Duchenne muscular dystrophy: What about lung function?

Abstract: Background Respiratory failure is the principal source of morbidity and mortality among patients with Duchenne muscular dystrophy exerting a negative influence on their total quality of life. The aim of this review is to provide systematically current literature evidence about the effects of different treatment options (available or under development) for Duchenne muscular dystrophy on the pulmonary function of these patients. Methods A comprehensive search was undertaken using multiple health‐related database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
2
0
1
Order By: Relevance
“…Most reviews used the seven bias domains listed in the tool. In five reviews, one domain was omitted or reported as ‘not applicable’ (domain 3, ‘classification of interventions’ [27] or 4, ‘deviations from intended interventions’ [28] , [29] , [30] , [31] ). One review used all seven domains, but added an eighth domain (‘vested interest bias’) [32] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reviews used the seven bias domains listed in the tool. In five reviews, one domain was omitted or reported as ‘not applicable’ (domain 3, ‘classification of interventions’ [27] or 4, ‘deviations from intended interventions’ [28] , [29] , [30] , [31] ). One review used all seven domains, but added an eighth domain (‘vested interest bias’) [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Most reviews used the seven bias domains listed in the tool. In five reviews, one domain was omitted or reported as ‗not applicable' (domain 3, ‗classification of interventions' [27] or 4, ‗deviations from intended interventions' [28][29][30][31]). One review used all seven domains, but added an eighth domain (‗vested interest bias') [32] One review appeared to use the seven ROBINS-I domains, but reported the results alongside results from the Cochrane RoB tool for RCTs, with domains renamed to fit both tools.…”
Section: Modifications and Non-standard Use Of Robins-imentioning
confidence: 99%
“…Although there is no definitive cure for DMD, the use of corticosteroids has been shown to improve respiratory muscle strength and delay the expected decline in lung function by decreasing inflammation-induced muscle damage. 31,[40][41][42] Thirty percent of our patients had history of taking corticosteroids, while the mean age of commencement of corticosteroids before and upon enrollment to the multidisciplinary clinic was 9 (±2.5) years. Research on the impact of corticosteroids in our patients is recommended in a more extended study period.…”
Section: Corticosteroidsmentioning
confidence: 97%
“…A fisiopatologia da DMD tem muitos aspectos e as principais causas de deficiência respiratória incluem disfunção da mecânica respiratória e doença do parênquima pulmonar (aspiração crônica ou pneumonia). Sendo assim, a capacidade de sustentar ventilação depende de um equilíbrio entre o desempenho dos músculos respiratórios e a carga respiratória (Gogou et al, 2020).…”
Section: Introductionunclassified